1999
DOI: 10.1021/bc990040w
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Anti-Tenascin Monoclonal Antibody−Streptavidin Conjugates for Pretargeting Applications

Abstract: Radioimmunopretargeting is based on the separate injection of a modified mAb and the radionuclide and most frequently exploits the very high avidity of biotin for streptavidin (SA). Currently, we are evaluating the therapeutic potential of directly labeled monoclonal antibody (mAb) 81C6, reactive with the extracellular matrix protein tenascin, in surgically created glioma resection cavity patients. To be able to investigate pretargeting in this setting, the synthesis of 81C6 mAb-SA conjugates was required. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…This unique form of RT delivery involves the use of radiolabeled antibodies targeting malignant brain tissue. Investigators at Duke University have been studying the efficacy of a 131-I-labeled murine anti-tenascin monoclonal antibody (131-I-m81C6) in the treatment of newly diagnosed and recurrent malignant brain tumors [67][68][69][70][71][72][73][74][75][76][77][78][79]. Tenascin is an extracellular matrix glycoprotein expressed ubiquitously in multiple tumor types, including high-grade gliomas, but not in normal brain tissue.…”
Section: Determining the Optimal Rt Field Sizementioning
confidence: 99%
“…This unique form of RT delivery involves the use of radiolabeled antibodies targeting malignant brain tissue. Investigators at Duke University have been studying the efficacy of a 131-I-labeled murine anti-tenascin monoclonal antibody (131-I-m81C6) in the treatment of newly diagnosed and recurrent malignant brain tumors [67][68][69][70][71][72][73][74][75][76][77][78][79]. Tenascin is an extracellular matrix glycoprotein expressed ubiquitously in multiple tumor types, including high-grade gliomas, but not in normal brain tissue.…”
Section: Determining the Optimal Rt Field Sizementioning
confidence: 99%
“…Specifically, poor imaging contrast and dose-limiting toxicity caused by conventionally radiolabeled mAbs can potentially be circumvented. 3,6,9 In the present studies, we developed a new pretargeting system, using cT84.66 for pretargeting CEA, which is highly expressed in colorectal, breast, and lung cancers. An SA conjugate of the mAb cT84.66 was synthesized, characterized, and evaluated for biotin pretargeting, using 111 In as an imaging radiometal and surrogate for pretargeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antibody pretargeting has been actively investigated as an alternative approach in recent years. [3][4][5][6][7][8][9] In pretargeting, a nonradioactive mAb-"receptor" construct is injected and allowed to reach maximum tumor uptake, after which a radiolabeled small molecule with high affinity and specificity for the mAb-"receptor" construct is administered. In this strategy, the mAb is decoupled from the radionuclide.…”
Section: Introductionmentioning
confidence: 99%
“…Chicoine and Silbergeld showed the ability of isolated cells from malignant gliomas to invade cerebral tissue in the C6 glioma model. Using fluorescent labeling of tumor cells in rodents, they demonstrated that individual neoplastic cells could be found more than 1 cm from the original tumor within 2 weeks of the initial implantation [24]. These cells retained the ability to begin new tumor nodules in soft agar, demonstrating that they continued their tumorogenicity.…”
Section: Invasion In Cerebral Gliomasmentioning
confidence: 99%
“…Invasion is the most troublesome attribute of malignant cerebral tumors for the surgeon [24,39,62,63]. Invasion of tumor cells has been demonstrated both in animal models and in human tumors.…”
Section: Invasion In Cerebral Gliomasmentioning
confidence: 99%